The role of γδT lymphocytes in atherosclerosis - Xu, LiMin; Chen, Fanfan; Fan, Wei; Saito, Suguru; Cao, DuoYao (Frontiers in Immunology, 2024)
Atherosclerosis poses a significant threat to human health, impacting overall well-being and imposing substantial financial burdens. Current treatment strategies mainly focus on managing low-density lipids (LDL) and optimizing liver functions. However, it’s crucial to recognize that Atherosclerosis involves more than just lipid accumulation; it entails a complex interplay of immune responses. Research highlights the pivotal role of lipid-laden macrophages in the formation of atherosclerotic plaques. These macrophages attract lymphocytes like CD4 and CD8 to the inflamed site, potentially intensifying the inflammatory response. γδ T lymphocytes, with their diverse functions in innate and adaptive immune responses, pathogen defense, antigen presentation, and inflammation regulation, have been implicated in the early stages of Atherosclerosis. However, our understanding of the roles of γδ T cells in Atherosclerosis remains limited. This mini-review aims to shed light on the characteristics and functions of γδ T cells in Atherosclerosis. By gaining insights into the roles of γδ T cells, we may uncover a promising strategy to mitigate plaque buildup and dampen the inflammatory response, thereby opening new avenues for effectively managing this condition.